(3OhQ GdGHJcGQi aj JMSjf COGA bWGY GdGJUGdGJ (B:s (3OQGSI ebGQfI Hjf GdLRGFQ heLehYI ef Ohd GdTQb GdChSW hTeGd EaQjbjG(B(MENA) /s - (3OGhOj, YHO GdaJGMs ((3JdeSGf(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2017)
(3GdEWGQ GdfXQj ddGHJcGQ (B-(3bWGY GdGJUGdGJ hYdGbJg HGdGHJcGQ (B-(3eDTQGJ GdGHJcGQ GdYGdej hBKGQgG Ydi bWGY GdGJUGdGJ aj Ohd GdTQb GdChSW hTeGd EaQjbjG (B-(3GdGHJcGQ hCKQg aj JMSjf GOGA bWGY GdGJUGdGJ aj GdLRGFQ hGdeZQH hJhfS hGdEeGQGJ GdeJMOI heUQ(B.s
(3HHdjhZQGajG(B:(3U(B.295s
Keywords: (3GdGHJcGQs; (3GdGJUGdGJs